ANALYSIS THE IMPACT OF HEALTH, EDUCATION, AND LABOR FORCE PARTICIPATION RATE (LFPR) ON LABOR PRODUCTIVITY IN 10 PRODUCTIVE DISTRICTS OR CITIES IN EAST JAVA (2019-2023) - Rina Agustina; Budi Prayitno; Eva Wany; Khoirul Abidin (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to analyze the influence of health, education, and the labor force participation rate (LFPR) on labor productivity in the ten most productive regencies/cities in East Java during the 2019–2023 period. Method: Employing a log-log panel data regression approach using the Fixed Effect Model (FEM), the study investigates the effects of Life Expectancy (LE), Average Length of Schooling (ALS), and LFPR on labor productivity, which is measured by the ratio of Gross Domestic Product (GDP) to the working population. Results: The findings reveal that LE and ALS exert a positive and statistically significant impact on productivity, reinforcing Becker and Grossman’s Human Capital theory. In contrast, LFPR demonstrates a negative and significant effect, suggesting that increased labor participation has not been matched by improvements in worker quality. Novelty: The study contributes to the empirical literature by emphasizing that LFPR is not merely a control variable but a crucial independent determinant of labor productivity. This insight underscores the importance of parallel investments in health and education to ensure that rising labor force participation translates into sustainable productivity gains.